Ben Marais (1909-1999) : the influences on and heritage of a South African Prophet during two periods of transformation - Hofmeyr, J.W. (Johannes Wynand), 1947- (University of Pretoria, 2013)
Thesis (DD)--University of Pretoria, 2005.